Emerging Functions of Human IFIT Proteins in Cancer - Pidugu, Vijaya Kumar; Pidugu, Hima Bindu; Wu, Meei-Maan; Liu, Chung-Ji; Lee, Te-Chang (Frontiers in Molecular Biosciences, 2019)
Interferon-induced protein with tetratricopeptide repeats (IFIT) genes are prominent interferon-stimulated genes (ISGs). The human IFIT gene family consists of four genes named IFIT1, IFIT2, IFIT3, and IFIT5. The expression of IFIT genes is very low in most cell types, whereas their expression is greatly enhanced by interferon treatment, viral infection, and pathogen-associated molecular patterns (PAMPs). The proteins encoded by IFIT genes have multiple tetratricopeptide repeat (TPR) motifs. IFIT proteins do not have any known enzymatic roles. However, they execute a variety of cellular functions by mediating protein-protein interactions and forming multiprotein complexes with cellular and viral proteins through their multiple TPR motifs. The versatile tertiary structure of TPR motifs in IFIT proteins enables them to be involved in distinct biological functions, including host innate immunity, antiviral immune response, virus-induced translation initiation, replication, double-stranded RNA signalling, and PAMP recognition. The current understanding of the IFIT proteins and their role in cellular signalling mechanisms is limited to the antiviral immune response and innate immunity. However, recent studies on IFIT protein functions and their involvement in various molecular signalling mechanisms have implicated them in cancer progression and metastasis. In this article, we focused on critical molecular, biological and oncogenic functions of human IFIT proteins by reviewing their prognostic significance in health and cancer. Research suggests that IFIT proteins could be novel therapeutic targets for cancer therapy.